Efektivitas Penerapan Hukum Acara Pidana dalam Menjamin Keadilan Bagi Terdakwa dan Korban - Dwi Putri Melati; Bagus Setiadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to evaluate the effectiveness of the application of criminal procedural law in ensuring justice for defendants and victims. Criminal procedural law has an important role in ensuring that the defendant's rights, such as the presumption of innocence and the right to self-defense, are fulfilled. On the other hand, this law must also protect the rights of victims, including providing justice and adequate recovery. However, in practice, there are various challenges that hinder its implementation, such as wrongful arrest, manipulation of the legal process, and lack of sensitivity towards victims. Using normative research methods, this study analyzes statutory regulations, legal doctrine, and concrete cases to assess the effectiveness of criminal procedural law. The research results show that the implementation of criminal procedural law in Indonesia still faces various obstacles, such as weak implementation of fair trial principles, slow legal processes, and lack of professionalism of law enforcement officials. This condition makes it difficult to achieve a balance of justice for the defendant and victim. This research recommends reforming the legal system, increasing the capacity of the apparatus, and strengthening victim protection mechanisms as an effort to increase the effectiveness of criminal procedural law in ensuring substantive justice.